Fifty years of ICAR-AICRPS: Spices, sustainability and the pursuit of sustainable development goals - Prasath, D; Sankar, S Mukesh; Aravind, Sharon; Nafid (Indian Horticulture, 2025)
Spices have been the cornerstone of India’s cultural and economic identity for millennia, attracting global demand from ancient civilizations to modern markets. The ICAR-All India Coordinated Research Project on Spices (AICRPS), based at ICAR-IISR in Kozhikode, began in 1971 and has evolved into India’s largest spices research network, spanning 38 centres across 14 agroclimatic zones and covering 17 spice crops. By advancing sustainable, equitable, and climate resilient practices, ICAR-AICRPS contributes meaningfully to the UN Sustainable Development Goals, including Zero Hunger, Gender Equality, and Responsible Production and Consumption.